Insilico analyses of heat shock protein (HSP 70) variation in Asian buffaloes - Maulana Tulus; Putra Widya Pintaka Bayu; Noor Ronny Rachman (BIO Web of Conferences)
Heat shock proteins (HSPs) constitute a category of molecular chaperones that play a crucial role in preventing non-specific protein aggregation and facilitating the refolding of cellular proteins to maintain homeostasis. This study analyzed the genomic and proteomic characteristics of HSP70 in six Asian buffalo breeds—Murrah, Diara, Iraqi, Kalahandi, Paralakhemund, and Banni—using the NCBI database, Clustal Omega for multiple sequence alignment, SWISS modeling, and phylogenetic analysis tools. Bioinformatics analysis indicated that the HSP70 gene in buffalo is localized on chromosome 2, comprising two exons separated by a single intron. In silico analysis using the Expasy translate tool identified that HSP70 encodes a protein consisting of 641 amino acids, with molecular weights ranging from 70.28 to 70.43 kDa. The findings further revealed that the HSP70 protein in Iraqi buffalo possesses 25 variable amino acid residues, while Diara and Banni buffalo exhibit seven and three variable amino acids, respectively. This study successfully identified and characterized HSP70 across six Asian buffalo breeds, highlighting that amino acid polymorphisms in Iraqi buffaloes may be associated with phylogenetic divergence and their adaptation to distinct climatic and geographical environments.